Insight into morphology dependent charge carrier dynamics in ZnSe–CdS nanoheterostructures. Issue 14 (29th March 2022) - Mittal, Mona; Dana, Jayanta; Lübkemann, Franziska; Ghosh, Hirendra N.; Bigall, Nadja C.; Sapra, Sameer
Abstract : The amount of hydrogen generation follows the order of NSs < NPs < NRs, emphasizing the effect of morphology on the enhancement of photo-induced charge separation and suppression of backward recombination. Abstract : Semiconductor nanoheterostructures (NHSs) are being increasingly used for the photocatalytic conversion of solar energy in which photo-induced charge separation is an essential step and hence it is necessary to understand the effect of various factors such as size, shape, and composition on the charge transfer dynamics. Ultrafast transient absorption spectroscopy is used to investigate the nature and dynamics of photo-induced charge transfer processes in ZnSe–CdS NHSs of different morphologies such as nanospheres (NSs), nanorods (NRs), and nanoplates (NPs). It demonstrates the fast separation of charge carriers and localization of both charges in adjacent semiconductors, resulting in the formation of a charge-separated (CS) state. The lifetime of the charge-separated state follows the order of NSs < NPs < NRs, emphasizing the effect of morphology on the enhancement of photo-induced charge separation and suppression of backward recombination. The separated charge carriers have been utilized in visible light driven hydrogen production and the hydrogen generation activity follows the same order as that for the lifetime of the CS state, underlining the role of charge separation efficiency. Therefore, the variation of the morphology of NHSs plays a significant role in their charge carrier dynamics and hence the photocatalytic hydrogen production activity.